I Wonder Why Pyramids Were Built And Other Questions About Ancient Egypt - Philip Steele
Browsers and young students alike will enjoy these lively question and answer books with their unique mix of realistic illustration and engaging cartoons. The enticing questions will amaze, amuse and inspire, while the highly visual format encourages kids to keep reading.